A Coupled FEM-BEM Methodology to Calculate 3-D Earth Surface Potentials Caused by HVDC Return Currents - Xu, Xiaowen; Li, Yiying; Yang, Shiyou (IEEE transactions on magnetics, 2024)
In the ground-return mode of high-voltage direct current (HVDC) transmissions, a large dc injected current in the earth will result in a rise in the earth surface potential (ESP), causing a dc bias in the power transformer and a dysfunction of the relay protection. Nevertheless, the accurate ESP calculation using the existing approaches will face challenges such as an extremely complex soil structure with inhomogenous mediums and a large-scale problem including an extremely small dimension of electrodes. To address the aforementioned issues, a novel coupled finite element-boundary element (BEM) method-based methodology is developed for the efficient and accurate calculation of 3-D ESP. In the proposed methodology, the finite element method (FEM) is used to solve the inhomogenous soil region while the BEM method is employed to solve the remaining layered homogeneous ones. An iterative solution methodology is proposed to implement the coupling of the two methods. Numerical examples on a case study are presented, illustrating the performance and advantages of the proposed method and its potentialities in engineering applications.